POTENSI, TANTANGAN DAN DUKUNGAN ANGGARAN DALAM OPTIMALISASI LAHAN RAWA MENJADI SAWAH UNTUK KEDAULATAN PANGAN - Dahiri Dahiri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Availability of swamps is still very extensive to be developed into rice fields, because the total land that has been developed has only reached 1.8 million hectares or only reached 5.39 percent. The purpose of this study was to find out the potential, challenges, and budget support for the optimization of swamps into rice fields. The research methods used were exploratory and descriptive methods. The results of the study show that there was potential swamp land to be developed into rice fields. Macro waterways is a major factor in rice farming. Also, there was problem associated with the standard of construction costs. Therefore, the President as the head of government must ensure coordination and cooperation between the Ministry of Agriculture and Ministry of Public Workd and Human Settlement in the swamp land optimization program to build macro channels. The two entities must be mutually coordinated so that macro and micro channels can be well-integrated. Secondly, the Government must change the standard construction costs for paddy fields that have been used so far because they do not reflect the characteristics and level of difficulty between regions. Standard costs obtained in intervals are minimum of Rp16.546.162 to a maximum Rp31.811.067.